2003
DOI: 10.1554/02-352
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeography and Introgressive Hybridization: Chipmunks (Genus Tamias) in the Northern Rocky Mountains

Abstract: If phylogeographic studies are to be broadly used for assessing population-level processes relevant to speciation and systematics, the ability to identify and incorporate instances of hybridization into the analytical framework is essential. Here, we examine the evolutionary history of two chipmunk species, Tamias ruficaudus and Tamias amoenus, in the northern Rocky Mountains by integrating multivariate morphometrics of bacular (os penis) variation, phylogenetic estimation, and nested clade analysis with regio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
58
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(62 citation statements)
references
References 86 publications
3
58
1
Order By: Relevance
“…amoneusDemboski and Sullivan, 2003, in the Inland Northwest). Furthermore, these studies have demonstrated that hybridization (between either species or subspecies) is the cause of incongruence (Good et al, 2003(Good et al, , 2008. The most comprehensive phylogenetic data set to date is that of Reid et al (2012), which we have reanalyzed in this study using relaxed-clock approaches (Figure 1).…”
Section: History Of Tamias Phylogeneticsmentioning
confidence: 99%
See 1 more Smart Citation
“…amoneusDemboski and Sullivan, 2003, in the Inland Northwest). Furthermore, these studies have demonstrated that hybridization (between either species or subspecies) is the cause of incongruence (Good et al, 2003(Good et al, , 2008. The most comprehensive phylogenetic data set to date is that of Reid et al (2012), which we have reanalyzed in this study using relaxed-clock approaches (Figure 1).…”
Section: History Of Tamias Phylogeneticsmentioning
confidence: 99%
“…Specifically, we examine one or more of four lines of evidence; these are ordered by level of rigor, with the last being the most explicit rejection of coalescent stochasticity. The first is the demonstration that the putatively introgressed haplotypes are geographically structured, which should not be the case for incongruence due to incomplete lineage sorting (Good et al, 2003). Second, congruence between morphology and nuclear microsatellite data (that is, correct assignment of individuals to morphologically defined taxa in Bayesian clustering analyses) support introgression of mtDNA in cases where the mtDNA gene tree is incongruent with morphology (Good et al, 2008;Hird and Sullivan, 2009;Reid et al, 2010).…”
Section: Detection Of Hybridizationmentioning
confidence: 99%
“…The number of recognized chipmunk species grew with the realization that contiguously allopatric taxa were often strikingly divergent in genital morphology (White 1953a, Callahan 1977, Sutton 1982, Patterson 1984. However, whereas preliminary studies at contact zones between chipmunk species indicated congruence between genital morphology, vocalizations, and pelage (Sutton and Nadler 1974, Patterson and Heaney 1987, Sutton 1987, Gannon and Lawlor 1989, Gannon and Stanley 1991, more sophisticated studies have documented complex cases of hybridization and introgression (Good and Sullivan 2001, Good et al 2003, Hird and Sullivan 2009, Hird et al 2010. Regional studies based on both nuclear and mitochondrial sequences have shown varying degrees of past introgression among an array of chipmunk species in western North America (Reid et al 2012, Sullivan et al 2014.…”
Section: Introductionmentioning
confidence: 99%
“…However, mtDNA is prone to introgression, or lateral transfer across species boundaries (e.g. Gyllensten & Wilson 1987;Tegelström 1987;Good et al 2003); therefore, lineage diagnoses are strongest when confirmed by nDNA variation or morphology (Wiens & Penkrot 2002;Morando et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Discordance between nDNA/morphology and mtDNA meanwhile is expected when introgression produces lateral transfer of genes between divergent populations (e.g. Gyllensten & Wilson 1987;Tegelström 1987;Good et al 2003). Introgression is also distinguished from incomplete lineage sorting by its characteristic geographical signal, with introgressed haplotypes being most common where the ranges of distinct populations abut one another (Harrison & Bogdanowicz 1997;Goodman et al 1999;García-París et al 2003).…”
Section: Introductionmentioning
confidence: 99%